Acute cardiac tamponade secondary to nonpenetrating injury from gunshot with beanbag round: A case report and literature review. (December 2022) - Schalet, Grant; Davis, Brooke; Gomez, Mario; Dickhudt, Timothy; Puente, Ivan
Abstract: Over the past twenty years, "less-lethal" munitions have caused a variety of significant, life-threatening injuries. However, evidence of blunt cardiac injury due to these weapons is sparse. A healthy 44-year old man presented with hemodynamic instability due to cardiac tamponade after he was shot with a beanbag, ultimately requiring operative intervention. This case report describes a unique clinical presentation of blunt cardiac injury and the diagnostic and therapeutic steps that the trauma surgery team took to appropriately manage this rare injury.